Genetic influences on the variability of response to repetitive transcranial magnetic stimulation in human pharyngeal motor cortex. Issue 7 (29th April 2019) - Raginis‐Zborowska, Alicja; Cheng, Ivy; Pendleton, Neil; Payton, Antony; Ollier, William; Michou, Emilia; Hamdy, Shaheen
Abstract: Background: Recent studies have reported substantial variability in response to repetitive transcranial magnetic stimulation (rTMS). We hypothesized that an individual's genetic predisposition may contribute to such variability in the pharyngeal motor cortex. This study aimed to investigate the response to 1 and 5 Hz rTMS paradigms on pharyngeal motor cortex in healthy participants and its relationship with genetic predisposition. Methods: Forty‐one healthy participants (25.4 ± 4.6 years old) received either or both 1 Hz (n = 39) and 5 Hz rTMS (n = 40) over pharyngeal motor cortex. Pharyngeal and thenar motor–evoked potentials were recorded at baseline and for 1 hour post‐rTMS. The participants were then classified according to their response. The associations between rTMS response and gender, time of day of the stimulation, and eight prespecified single nucleotide polymorphisms (SNPs) were analyzed. Key Results: There was no direction‐specific response to either paradigm (1 Hz: F [3.69, 129.21] = 0.78, P = 0.56; 5 Hz: F [4.08, 146.85] = 1.38, P = 0.25). Only 13% of participants showed the expected bidirectional response (inhibition for 1 Hz and excitation for 5 Hz). Significant associations were found between response and COMT (1 Hz: P = 0.03) and DRD2 (1 Hz: P = 0.02; 5 Hz: P = 0.04) polymorphisms. Carriers of minor allele G from SNP rs6269 ( COMT ) were more likely to show inhibitory or excitatory outcomes after 1 Hz rTMS. By contrast, carriers of minor allele A from SNP rs1800497 ( DRD2 ) were more likely to show no response to 1 Hz rTMS and inhibition after 5 Hz rTMS. Conclusions & Inferences: Two SNPs from COMT and DRD2 genes may partially explain the response variability to rTMS in the pharyngeal motor system. Further research should focus on stratified approaches for neurostimulatory dysphagia treatment using rTMS. Abstract : The response to 1 and 5 Hz repetitive transcranial magnetic stimulation varies substantially among individuals. We found that the response was associated with polymorphisms in the genes COMT and DRD2. Our findings suggested that genetic variation may partially explain the observed response variability.